Greenhouse vegetable production: Hydroponic Systems - Marr, Charles W. (My University, 2016)
Many people think of hydroponics as growing plants in water, but hydroponic production actually is defined as growing plants without soil. This production system may use a wide variety of organic and inorganic materials. The nutrient solution, rather than the media in which the plants are growing, always supplies most of the plant nutrient requirements. This method of growing has also been referred to as nutrient-solution culture, soilless culture, water culture, gravel culture and nutriculture.
Charles W. Marr, Greenhouse vegetable production: Hydroponic Systems, Kansas State University, September 1994.
Keywords: Hydroponics; Liquid (Non-Aggregate) Hydroponic Systems; Nutrient Film Technique (Nft); Aggregate Hydroponic Systems; Bag Culture; Nutrient Solution